Torn between America and China : Elite Perceptions and Indonesian Foreign Policy - Novotný, Daniel, 1973- (Book collections on Project MUSE., 2010)
How can a developing, democratic and predominantly Muslim country like Indonesia manage its foreign relations, while facing a myriad of security concerns and dilemmas in the increasingly complex post-Cold War international politics, without compromising its national interests and sacrificing its independence? Approaching this problem from the vantage point of the Indonesian foreign policy elite, this book explores the elite's perceptions about other states and the manner in which these shape ...